Predictors of Chronic Opioid Use: A Population-Level Analysis of North Carolina Cancer Survivors Using Multi-Payer Claims. (21st April 2021) - Check, Devon K; Baggett, Christopher D; Kim, KyungSu; Roberts, Andrew W; Roberts, Megan C; Robinson, Timothy; Oeffinger, Kevin C; Dinan, Michaela A
Abstract: Background: No population-based studies have examined chronic opioid use among cancer survivors who are diverse with respect to diagnosis, age group, and insurance status. Methods: We conducted a retrospective cohort study using North Carolina cancer registry data linked with claims from public and private insurance (2006-2016). We included adults with nonmetastatic cancer who had no prior chronic opioid use (n = 38 366). We used modified Poisson regression to assess the adjusted relative risk of chronic opioid use in survivorship (> 90-day continuous supply of opioids in the 13-24 months following diagnosis) associated with patient characteristics. Results: Only 3.0% of cancer survivors in our cohort used opioids chronically in survivorship. Predictors included younger age (adjusted risk ratio [aRR] 50-59 vs 60-69 = 1.23, 95% confidence interval [CI] = 1.05 to 1.43), baseline depression (aRR = 1.22, 95% CI = 1.06 to 1.41) or substance use (aRR = 1.43, 95% CI = 1.15 to 1.78) and Medicaid (aRR vs private = 1.93, 95% CI = 1.56 to 2.40). Survivors who used opioids intermittently (vs not at all) before diagnosis were twice as likely to use opioids chronically in survivorship (aRR = 2.62, 95% CI = 2.28 to 3.02). Those who used opioids chronically (vs intermittently or not at all) during active treatment had a nearly 17-fold increased likelihood of chronic use in survivorship (aRR = 16.65, 95% CI = 14.30 to 19.40). Conclusions: Younger and low-income survivors, those with baseline depression or substance use, and those who require chronic opioid therapy during treatment are at increased risk for chronic opioid use in survivorship. Our findings point to opportunities to improve assessment of psychosocial histories and to engage patients in shared decision-making around long-term pain management, when chronic opioid therapy is required during treatment.